Telaah terhadap Kesederhanaan Redaksi Tafsir Jalalain dan Dampaknya bagi Pemula Studi Tafsir - Rizal; Rahmad Dzailani Al Thamim; Rasyid Hidayatullah; Akhmad Dasuki (PT. Saha Kreasi Indonesia, 2025)
This study aims to examine the characteristics of the concise diction in Tafsir al-Jalalain and to assess its impact on beginner readers in the study of Qur’anic exegesis. This research employs a qualitative method through library research by exploring relevant academic literature, which is then analyzed descriptively and analytically to identify the ijmālī interpretive patterns underlying the composition of the tafsir. The findings indicate that the simplicity of Jalalain’s diction represents a methodological strategy intended to facilitate readers in grasping the essential meaning of verses quickly and systematically, thereby making it effective as a foundational resource for early Qur’anic learning. However, this concise nature also presents limitations, particularly in terms of contextual breadth and analytical depth, thus requiring the support of more comprehensive references. The study concludes that the concise diction of Jalalain holds significant pedagogical value for beginners, while simultaneously underscoring the need for adaptive learning approaches to ensure the development of a more holistic understanding of Qur’anic interpretation.